Recovering external contribution from the monthly mean series of a given geomagnetic observatory - Bejo Duka; Eni Duka; Klaudio Peqini (Annals of Geophysics, 2016)
The differences between monthly mean values of the observed geomagnetic field and monthly values predicted by different models of the internal geomagnetic field (named “model biases”) for the time period 2000-2015 at several geomagnetic observatories are analyzed. We notice that increasing the maximum degree of the model is not always followed by the decrease of such “model bias”. The time series of these “model biases” reduced by their average resulted to be approximately the same for all models and should represent the external (non-modeled) contribution to the observed geomagnetic field. These time series for different observatories (close or away to each other) are compared and their power spectra are analyzed. Such spectra have common features like the annual and semi-annual variation with some possible sporadic cases of seasonal variation.